An Open Platform for RGB Composite Analysis and Validation: RGB_DIGI - A. N. Arslan; A. N. Arslan; C. M. Tanis (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
In this paper we present an open platform which consists of a free automated digital image processing tool, a camera network portal where digital images are available freely, operational monitoring system and Cal / Val activities producing near real time results for comparison of satellite-derived products with webcam derived and in-situ data. We proposed a concept of RGB-based data platform which may provide some progresses to existing challenges of applications of digital imagery technologies. We provided a quick analysis from a set of webcam images and discuss their capabilities on capturing climate proxies in 10 years’ time.